The merger of populations, the incidence of marriages, and aggregate unhappiness - Oded Stark; Franz Rendl; Marcin Jakubek (University of Tübingen, Faculty of Economics and Social Sciences, 2011)
Let a society's unhappiness be measured by the aggregate of the levels of relative deprivation of its members. When two societies of equal size, F and M, merge, unhappiness in the merged society is shown to be higher than the sum of the levels of unhappiness in the constituent societies when apart; merger alone increases unhappiness. But when societies F and M merge and marriages are formed such that the number of households in the merged society is equal to the number of individuals in one of the constituent societies, unhappiness in the merged society is shown to be lower than the aggregate unhappiness in the two constituent societies when apart. This result obtains regardless of which individuals from one society form households with which individuals from the other, and even when the marriages have not (or not yet) led to income gains to the married couples from increased efficiency, scale economies, and the like. While there are various psychological reasons for people to become happier when they get married as opposed to staying single, the very formation of households reduces social distress even before any other happiness-generating factors kick in.
urn:nbn:de:bsz:21-opus-56496
Keywords: D0; D10; D31; D63; 330; Merger of populations; Integration of societies; Unhappiness; Marriages; Relative Deprivation